2018
DOI: 10.2298/jmmb170711050y
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and separation of iron from iron ore using innovative fluidized magnetization roasting and magnetic separation

Abstract: In this investigation, a pilot-scale fluidized magnetization roasting reactor was introduced and used to enhance magnetic properties of iron ore. Consequently, the effects of roasting temperature, reducing gas CO flow rate, and fluidizing gas N2 flow rate on the magnetization roasting performance were studied. The results indicated that the hematite was almost completely converted into magnetite by a gas mixture of 4 Nm3/h CO and 1 Nm3/h N2 at roasting temperature of 540?C for about 30 s. Under optimized condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In response to the problems existing in the prior technologies, a new concept of "peroxidationregenerative reduction-reoxidation" suspension magnetizing roasting was proposed by Northeastern University (NEU) [48][49][50][51][52][53][54][55][56][57][58][59][60]. Further, a new type of suspension roasting pilot-scale test equipment has been successfully developed.…”
Section: Development Of Fluidized Bed Magnetizing Roasting Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…In response to the problems existing in the prior technologies, a new concept of "peroxidationregenerative reduction-reoxidation" suspension magnetizing roasting was proposed by Northeastern University (NEU) [48][49][50][51][52][53][54][55][56][57][58][59][60]. Further, a new type of suspension roasting pilot-scale test equipment has been successfully developed.…”
Section: Development Of Fluidized Bed Magnetizing Roasting Technologymentioning
confidence: 99%
“…Based on this innovative process and equipment, the suspension magnetizing roasting laboratory and semi-industrial tests have been conducted on iron ore resources domestically and overseas [48][49][50][51][52][53][54][55][56][57][58][59], such as the Ansteel eastern tailings, Donganshan iron ore, JISCO fine ore, tailings and lump ore, and Sierra Leone iron ore. The results are summarized in Table 3.…”
Section: Development Of Fluidized Bed Magnetizing Roasting Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetization roasting, including rotary kiln magnetization roasting, shaft furnace magnetization roasting, and suspension magnetization roasting, is regarded as an effective method to treat refractory iron ores (Yu et al, 2018a). Among them, suspension magnetization roasting has obvious advantages in terms of full gas-solid contact, high mass transfer and heat transfer efficiency, and low roasting energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, previous studies showed that the fluidized bed technology provides the advantages of uniform temperature and high efficiency of heat and mass transfer. The hematite in iron ores can be converted to magnetite and magnetic properties will be greatly enhanced by using fludized magnetization raosting [22]. The fluidized bed technology is being widely used in many industries and fields of applications [23][24][25].…”
Section: Introductionmentioning
confidence: 99%